Alun-Alun sebagai Ruang Ekonomi: Dinamika Pendapatan UMKM dalam Perspektif Ekonomi Islam - Claudyea Fatimatuh Zuhro; M. Dayat; Ifdlolul Maghfur (Kartika: Jurnal Studi Keislaman, 2026)
The town square serves vital social and economic functions, providing public space for community recreation and micro, small, and medium enterprises (MSMEs). This study analyzes the impact of Alun-Alun Mojo Kepuh on MSME activities and income in Sedati Village, Ngoro District, Mojokerto Regency, through an Islamic economic perspective, while identifying key facilities driving this growth. Data were collected via observations, interviews, and documentation with MSME operators, visitors, and managers. Analysis techniques included data reduction, data display, and conclusion drawing. The results demonstrate that Alun-Alun Mojo Kepuh significantly boosts MSME business activities and income by increasing visitor numbers, business capital, and overall economic dynamics. From an Islamic economic viewpoint, the town square operationalizes the principles of falah (well-being), distributive justice, and maslahah mursalah (public interest) by delivering tangible economic benefits. Key facilities influencing MSME growth include children's play areas, seating spaces, and entertainment events like night markets. These amenities enhance regional appeal, extend visitor stay duration, and stimulate consumer participation in MSME activities near the square